Structure of bacterial communities in phosphorus-enriched rhizosphere soils - Yuwei Hu (2020)
© 2020 by the authors. Although phytoremediation is the main method for P-removal and maintaining ecosystem balance in geological phosphorus-enriched soils (PES), little is known about the structure and function of microbial communities in PES. Interactions between plants and soil microorganisms mainly occur in the rhizosphere. The aim of this work was to investigate the composition and diversity of bacterial communities found in rhizosphere soils associated with the following three dominant plant species: Erianthus rufipilus, Coriaria nepalensis, and Pinus yunnanensis. In addition, we compared these rhizosphere bacterial communities with those derived from bulk soils and grassland plots in PES from the Dianchi Lake basin of southwestern China. The Illumina MiSeq platform for high-throughput sequencing of 16S rRNA was used for the taxonomy and the analysis of soil bacterial communities. The results showed higher bacterial diversity and nutrient content in rhizosphere soils as compared with bulk soils. Rhizosphere bacteria were predominantly comprised of Proteobacteria (24.43%) and Acidobacteria (21.09%), followed by Verrucomicrobia (19.48%) and Planctomycetes (9.20%). A comparison of rhizosphere soils of the selected plant species in our study and the grassland plots showed that Acidobacteria were the most abundant in the rhizosphere soil of E. rufipilus; Bradyrhizobiaceae and Rhizobiaceae in the order Rhizobiales from C. nepalensis were found to have the greatest abundance; and Verrucomicrobia and Planctomycetes were in higher abundance in P. yunnanensis rhizosphere soils and in grassland plots. A redundancy analysis revealed that bacterial abundance and diversity were mainly influenced by soil water content, soil organic matter, and total nitrogen.